1995
DOI: 10.1161/01.hyp.25.4.848
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Nitric Oxide (Nitrite/Nitrate) Levels in Postmenopausal Women Substituted With 17β-Estradiol and Norethisterone Acetate

Abstract: Postmenopausal women (PMW) have an increased risk of cardiovascular disease that is attenuated by hormone replacement therapy (HRT). Inasmuch as hypertension and atherosclerosis are associated with diminished endothelium-derived nitric oxide (NO), we investigated whether HRT augments NO release in PMW. We determined serum levels of nitrite/nitrate (NO2 + NO3) at baseline and during the 6th, 12th, and 24th months of the study in two groups of PMW. One group (HRT-PMW, n = 13) received continuous transdermal admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
1
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(116 citation statements)
references
References 27 publications
7
106
1
2
Order By: Relevance
“…18,52 However, by comparison to other osteoporosis-like phenotype models eNOSϪ/Ϫ mice are distinct. For example, osteoprotegerin-gene-deficient mice demonstrate an early onset osteoporosis-like phenotype, 53 similar to eNOSϪ/Ϫ mice but is because of increased osteoclast numbers and resorption rather than attenuated osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
“…18,52 However, by comparison to other osteoporosis-like phenotype models eNOSϪ/Ϫ mice are distinct. For example, osteoprotegerin-gene-deficient mice demonstrate an early onset osteoporosis-like phenotype, 53 similar to eNOSϪ/Ϫ mice but is because of increased osteoclast numbers and resorption rather than attenuated osteoblast activity.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, acute administration of oestrogen improves vasodilatation induced by acetylcholine in coronary arteries [23,24]. The assumption that this improvement in EDV is mediated by the NO system is further strengthened by the finding that oestrogen supplementation increased the levels of nitrate and nitrite, the breakdown products of NO, in postmenopausal women [25].…”
Section: Discussionmentioning
confidence: 99%
“…[40][41]44 Studies have shown that synthetic progestogens may exert a relative vasoconstrictor effect on the vasculature, the magnitude of the effect being proportional to the relative 'androgenicity' of the individual preparation. [40][41][42]44 In contrast to the vasoconstrictor effects observed with the 'androgenic' progestogens, the 'non-androgenic' progestogens including progesterone and medroxyprogesterone (which was used in the current study) have been shown to have a net vasodilator effect. 38,41,44 The observations in the present study examining the dose-response of cyclical MPA in the presence of a fixed replacement dose of oestrogen are consistent with MPA having either no net effect on vascular tone or a small net vasodilator effect.…”
Section: Discussionmentioning
confidence: 64%
“…37 The magnitude of any progestogen-related effect may also be influenced by the relative androgenicity of the progestogen preparation used. [40][41][42][43][44] In the present study in normotensive postmenopausal women, a randomised, double-blind crossover design was used to compare with placebo the effects on blood pressure and other cardiovascular parameters of cyclical doses spanning the clinical dose range of the C21 progestogen, medroxyprogesterone acetate, in normotensive women receiving a fixed mid-range daily dose of conjugated equine oestrogen. The study tested the null hypothesis that there would be no significant effect on blood pressure from the addition of 'replacement' doses of exogenous semi-synthetic progestogen as cyclical therapy to daily oestrogen supplementation in postmenopausal normotensive women.…”
Section: Introductionmentioning
confidence: 99%